Vitellogenin expression corresponds with reproductive status and caste in a primitively eusocial bee. (November 2020) - Awde, David N.; Skandalis, Adonis; Richards, Miriam H.
Graphical abstract: Highlights: Vg mRNA levels are associated with phenotypic variation in social insect castes. Traits associated with vg vary during a breeding season in eusocial sweat bees. We compared vg levels in castes of a sweat bee species during a breeding season. Vg expression was associated with ovarian development and therefore with caste. Females without ovarian development expressed vg while males did not. Abstract: Vitellogenin ( vg ) expression is consistently associated with variation in insect phenotypes, particularly egg-laying. Primitively eusocial species, such as eusocial sweat bees, have behaviourally totipotent castes, in which each female is capable of high levels of ovarian development. Few studies have investigated vg expression patterns in primitively eusocial insects, and only one study has focused on a primitively eusocial bee. Here we use a primitively eusocial sweat bee, Lasioglossum laevissimum, and Real Time quantitative PCR (RT-qPCR) to investigate the relationship between vg expression, castes, and variation in phenotypes associated with castes differences. These assays showed that females with high ovarian development had the highest levels of vg expression, and that vg expression levels reflected the reproductive status of females first and caste second. This is in contrast to vg expression patterns observed in advanced eusocial queens and workers, which differ in vg expression based on caste and have caste-specific vg expression patterns. Furthermore, future queens (gynes) do not have ovarian development and had similar vg expression levels to early spring foundresses, which do have ovarian development, supporting Vg's function as a transporter of lipids and amino acids before diapause.